Medieval Timber Motte Towers. Issue 1 (2nd January 2018) - Wyeth, William
Abstract : TIMBER TOWERS, raised at castles and on mottes, have not been subject to the kind of extensive research coverage given to masonry examples. This article examines the evidence for medieval timber motte towers in Britain. Their shape and dimensions are discussed and their durability. The use of timber is explored in terms of its contribution to the tangible and intangible qualities of towers and fortifications. The article concludes with an examination of Hen Domen in Wales, and demonstrates that a broader approach to understanding these features can provide insights on medieval expressions of lordship and authority.